Bioenergy in the era of circular economy: Anaerobic digestion technological solutions to produce biogas from lipid-rich wastes. (May 2021) - Diamantis, Vasileios; Eftaxias, Alexandros; Stamatelatou, Katerina; Noutsopoulos, Constantinos; Vlachokostas, Christos; Aivasidis, Alexandros
Abstract: The circular economy model has gained increasing attention in policy agenda in modern times of climate change and decarbonisation. Undeniably, reintroducing waste in supply chains and cover energy needs for local communities and enterprises assists to rational management of waste, promotes resource efficiency and properly applies the circular model. Biogas is a major vehicle for producing bioenergy in the frames of modern bioeconomy. In this short review, the fundamentals and the technology for biogas production from lipids and lipid-rich wastes are meticulously and critically discussed. Anaerobic digesters with external sludge separation and recycling are the mainstream option for the treatment of lipid-rich wastes. These systems retain both microorganisms and the lipids adsorbed onto the anaerobic biomass, thus improving the methane yield. Anaerobic membrane bioreactors can completely avoid the washout of microorganisms and enhance the retention of lipids, however membrane fouling often deteriorates hydraulic performance. The review clearly depicts that data from the operation of full-scale facilities treating lipid-rich wastes are scarce in the literature. Effort is required by all stakeholders (practitioners, companies, scientists and politicians) to leverage the penetration of anaerobic technologies, to exploit lipid-rich wastes in order to efficiently promote renewable bioenergy and support bioeconomy. Graphical abstract: Image 1 Highlights: The fundamentals and the technology for biogas production from lipids are reviewed. Lipids pre-treatment is a prerequisite for achieving high-rate anaerobic digestion. Anaerobic digesters with external sludge separation can increase biogas yield. Anaerobic membrane bioreactors enable complete retention of microorganisms and lipids. Increased penetration of anaerobic technologies to exploit lipid-rich wastes is necessary.